Effects on extraordinary transmission of TE wave through varying structure of sub-wavelength metallic gratings without host media - 王亚伟 陈馀娇 孟增辉 尚学府 金卫凤 卜敏 徐媛媛 朱兴龙 (Optoelectronics letters, 2013)
A model of sub-wavelength metallic grating without host media is proposed. Under the excitation of TE polarized light, the extraordinary transmission is also found, and their transmission energy distributions corresponding to different structural parameters of this model are calculated systematically by using f＇mite difference time domain （FDTD） method. The influence of slit width, grating thickness and grating period on the location of transmission peak is obtained. By studying these relations, it is found that Fabry-Perot-like （FPL） effect of the slit is the main physical reason of this extraordinary transmission. Varying the slit width can cause the change of reflection phase transition at both ends, and then the characteristics of FPL resonance of slit cavity are affected. The surface mode of metallic gratings has less effect on the location of transmission peak.